Female sexual dysfunction: A comparative study in drug naive 1(st) episode of depression in a general hospital of South Asia - Roy, Payel (Indian J Psychiatry, 2015)
BACKGROUND: Women's sexual dysfunction is found to be highly prevalent in western and Indian literature. Limited studies are available on drug naive depression in western literature and in Indian population. AIM: To determine the prevalence rate and symptom profile of female sexual dysfunctions in patients with untreated depression. DESIGN: A cross-sectional study in the psychiatry out-patient department of general hospital in South India. MATERIALS AND METHODS: Following written informed consent female sexual functioning index (FSFI) and Arizona Sexual Experience Scale (ASEX) – female version and Hamilton Depression Rating Scale (HAMD - 17 item) on 30 cases and 30 controls was administered. Sociodemographic data, pattern and type of sexual dysfunctions were enquired. Data were analyzed using descriptive statistics, contingency co-efficient analysis and stepwise multiple regression. RESULTS: The mean score of HAMD 17 item in study group was 19.13. The study showed that female sexual dysfunction was 70.3% in study group compared to 43.3% in control FSFI scores above 16 in HAMD had dysfunction of 76% with FSFI in study group. With ASEX-F sexual dysfunction was 73.3% in study compared to 20% in control. Scores above 16 in HAMD had 80% of sexual dysfunction with ASEX-F in study group. CONCLUSION: The study found that ASEX-F co-related better with HAMD 17 item. Following the onset of depression, the incidence of sexual dysfunction started at an early age in women.